Issues faced while translating Folkloric Material from the English into Tamil - Mathura, S. (My University, 2021)
Translation is not merely an inter-linguistics activity, but also an inter-cultural activity. Since folklore is a vital part in literary texts to institute a cultural system, due to its complex nature several challenges are faced by the translators. This study aims to investigate the linguistic and cultural issues faced by the undergraduates of the Department of Translation Studies, Faculty of Arts, University of Jaffna, while translating folklore material form the English in to Tamil. The objective of the study was to identify the techniques and strategies used by the translator to overcome the problems. The cultural problems were categorized as problems in translating idioms, proverbs and cultural bound terms. the linguistic problems were categorized as complex sentence structure, terminological problems and problems caused due to punctual marks. In order to overcome the problems several translation procedures were used by the students. Accordingly, qualitative methodology and quantitative methodology were used to bring out the study. Quantitative methodology was used to collect the data. In qualitative methodology comparative method was used to compare the source text and the translation whereas descriptive method was used to describe the outcomes of the study. As the focus was on folkloric material it draws attention to the requirement of observing the ethnography of language in trying to reproduce the most exact approximation of the nuances in the original. The findings of the study could help the students in translation studies and researches who deal with issues in translating Folkloric Material from the English into Tamil to find the appropriate ways to handle such problems.
Keywords: Cultural problem; Folkloric Material; Translation; Linguistic problem; Undergraduates